PENYULUHAN TENTANG PELUANG USAHA GUNA MENUMBUHKAN KEMANDIRIAN EKONOMI IBU RUMAHTANGGA KELURAHAN GEDANGANAK, KECAMATAN UNGARAN TIMUR, KABUPATEN SEMARANG - Endang Rusdianti; Sri Purwantini; Paulus Wardoyo (Jurnal Pengabdian Kepada Masyarakat (J-ABDIMAS), 2020)
The increasing expenditure of the mother's household in Gedanganak is felt along with the increase in the price of daily necessities. In general, housewives are still less creative in dealing with household expenses. Most housewives are still monotonous in managing their household finances and have not been able to fill their spare time with productive businesses. Therefore it is necessary to have enlightenment on how best to anticipate business opportunities and provide examples of how to fill useful free time. One of the solutions provided by the team is to provide counseling on business opportunities and the practice of making dishwashing soap in the hope that it can help reduce family economic expenses and as a way to open business opportunities that can be run. In addition, information from village officials, in general, housewives still rely on their husbands as the main source of income. This is an interesting phenomenon for counseling about the importance of fostering economic independence by taking advantage of new business opportunities for housewives. After attending the counseling and practice of making dish soap, participants are expected to be more creative in taking advantage of business opportunities so that their household economic independence will grow and for those who already have a business, it is hoped that their business will increase.